Chemical relaxation in porous ionic–electronic conducting materials represented by the distribution of characteristic times. Issue 34 (17th August 2020) - Zhang, Yanxiang; Yan, Fuyao; Hu, Bobing; Xia, Changrong; Yan, Mufu
Abstract : Distribution of characteristic times (DCT) is proposed to resolve chemical relaxation in porous MIECs and to estimate kinetic parameters. Abstract : High-temperature catalytic and transport properties of porous ionic–electronic conducting materials (MIECs) are vital for device-level performance and are sensitive to microstructure, however they are indirectly characterized using dense MIECs with simple geometry. The structure–property relationship can be misinterpreted, as the fabrication procedures and microstructures of the dense MIECs are different from those of the porous MIECs. Here, the distribution of characteristic times (DCT) is proposed to resolve chemical relaxation (CR) kinetics in porous MIECs. The peak in a DCT spectrum has a clear physical origin, with its integral area being the fractional volume involved. In contrast to previous treatments that assume surface exchange-limited kinetics, the DCT spectra of porous La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ (LSCF) show that gaseous oxygen diffusion can dominate the CR kinetics in 0–40 percent volume, depending on the sintering temperature of the sample. The surface exchange coefficient and its thermal activation energy are much lower than those of the dense bulk LSCF. These findings indicate a different catalytic mechanism on the internal surface of porous LSCF, compared to in the dense bulk material. The DCT approach opens up a way to reveal the CR kinetics in porous MIECs, and can readily be extended from e − /O 2− to e − /H + and e − /H + /O 2− conducting oxides.